1994
DOI: 10.1007/bf00173032
|View full text |Cite
|
Sign up to set email alerts
|

Time course of technetium-99m sestamibi myocardial distribution in dogs with a permanent or transient coronary occlusion

Abstract: The influence of duration of coronary occlusion and reperfusion on technetium-99m hexakis-2-methoxyisobutylisonitrile (99mTc-sestamibi) myocardial redistribution between necrotic, salvaged and non-ischaemic myocardium was investigated in dogs submitted either to a 90-min or a 24-h permanent left descending coronary artery occlusion (groups 1 and 2) or to a 90-min occlusion followed by 30 min, 6 h or 22.5 h of reperfusion (groups 3, 4 and 5). In all groups, 99mTc-sestamibi and radiolabelled microspheres were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…However, a number of other investigators have questioned the utility of 99m Tc-sestamibi for assessment of myocardial viability [13][14][15][16][17][18][19][20][21][22]. Once again, models have ranged from cultured cells to perfused hearts, large animal models, and patient studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, a number of other investigators have questioned the utility of 99m Tc-sestamibi for assessment of myocardial viability [13][14][15][16][17][18][19][20][21][22]. Once again, models have ranged from cultured cells to perfused hearts, large animal models, and patient studies.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that the initial uptake reflects predominantly coronary blood flow, independent of myocardial viability. A number of reports using pig and dog models of coronary occlusion followed by reperfusion also found a poor correlation of 99m Tc-sestamibi uptake with viability [13,14,18,19,21]. Despite a 24-h model of coronary occlusion, Merhi et al concluded that 99m Tc-sestamibi distribution was not significantly influenced by cell death [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations